Western Sahara: A Frozen Conflict - Chavez Fregoso, Carolina; Živković, Nikola (Journal of Regional Security, 2018)
The conflict in the Western Sahara is one of the oldest and most neglected. It is a conflict that moves yet fails to transform. It includes a number of internal and external traits, a high involvement of external actors and, apparently, no real desire to negotiate, impeding the disputing parties from transforming their initial positions that render this conflict frozen. It is a conflict in which, despite decades of negotiations and the expressed desire to reach a resolution (whether by autonomy, annexation or independence), economic and political interests, identities and the influence of foreign relations seem to obstruct rather than contribute to the conflict transformation. This article offers arguments that explain the Western Sahara conflict as a frozen one, and argues that acknowledgment of this reality is necessary to enable a conflict transformation that would contribute to the security of the region of North Africa.